Swiss recommendations on perioperative antimicrobial prophylaxis in children (Swiss Medical Weekly, 2022)
Infection following surgical procedures leads to significant morbidity and mortality in all age groups. Sterile techniques, antibiotic prophylaxis and improved postoperative wound care have contributed to the decline of surgical site infections since the early days of surgery. Recommendations on the use of perioperative antimicrobial prophylaxis exist for adults, but are rare for the paediatric population. Here, we provide a standardised approach to the effective use of antimicrobial agents for the prevention of surgical site infections in children contributing to a targeted and rational perioperative use of antibiotics in Switzerland.